CORRELATION BETWEEN HEMOGLOBIN A1c (HbA1c) LEVELS AND MICROALBUMINURIA IN DIABETES MELLITUS PATIENTS AT PRODIA SUNTER - Putri, Maylina; Putra, I Gusti Putu Agus Ferry Sutrisna; Prihatiningsih, Diah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Diabetes Mellitus (DM) is a disease caused by pancreatic failure in performing its function of producing insulin. A lack of insulin will lead to an increase in blood glucose levels, also known as hyperglycemia. Hemoglobin A1c and microalbuminuria are screening examinations used to detect the early onset of diabetic nephropathy. Diabetic nephropathy is defined as a clinical syndrome in diabetes mellitus patients characterized by persistent albuminuria, an irreversible decrease in glomerular filtration rate, and increased arterial blood pressure. The purpose of this study is to determine the relationship between Hemoglobin A1c and microalbuminuria in diabetes mellitus patients at Prodia Sunter. The research method used is quantitative analytic with a cross-sectional approach. The data collected were secondary data from the period of January–July 2024 with a total of 60 samples. Sampling was conducted using purposive sampling and met the inclusion criteria, namely patients over 60 years of age, Hemoglobin A1c value ≥7, diagnosed with diabetes mellitus, no history of thalassemia, and who had undergone Hemoglobin A1c and microalbuminuria examinations. The results of this study show a significant unidirectional positive relationship with a very strong correlation between Hemoglobin A1c levels and microalbuminuria in diabetes mellitus patients, with sig (2-tailed) = 0.000 and correlation coefficient value = 0.892. The relationship between Hemoglobin A1c levels and microalbuminuria is unidirectional positive, meaning that the higher the Hemoglobin A1c levels, the higher the microalbuminuria levels.